1965
DOI: 10.1029/jz070i006p01441
|View full text |Cite
|
Sign up to set email alerts
|

Attenuation of seismic energy in the upper mantle

Abstract: Abstract. The amplitude attenuation and phase dispersion for Love and Rayleigh waves in the period range 50 to 300 sec is determined from two earthquakes by digital techniques.A distribution of Q, or anelasticity, is determined for the upper mantle which satisfies the amplitude decay data for Love and Rayleigh waves and which is consistent with available body wave data. An argument is made for a longitudinal wave Q of about 2.4 to 2.6 times the Q for shear waves. This implies that very small losses are im·olve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
151
0
1

Year Published

1966
1966
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 387 publications
(161 citation statements)
references
References 12 publications
9
151
0
1
Order By: Relevance
“…These perturbations can, in turn, be used for the calculation of the attenuation of surface waves as a function of period for realistic anelastic earth models [Anderson and Archam-1964;Anderson et al, 1965]. Integral relations similar to (7) and (8) can also be obtained for the medium response.…”
Section: Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…These perturbations can, in turn, be used for the calculation of the attenuation of surface waves as a function of period for realistic anelastic earth models [Anderson and Archam-1964;Anderson et al, 1965]. Integral relations similar to (7) and (8) can also be obtained for the medium response.…”
Section: Symbolsmentioning
confidence: 99%
“…(c) The attenuation of surface waves, given the variation of anelasticity with depth [Anderson and Archambeait, 1964;Anderson et al, 1965].…”
Section: Introductionmentioning
confidence: 99%
“…Surface-wave attenuation studies for the Pacific and Atlantic Oceans have provided a good knowledge of the Q structure under both oceans (e.g., ANDERSON et al, 1965;TSAI and AKI, 1969;MITCHELL, 1976;MITCHELL et al, 1976). Local and regionalized studies in these oceans (e.g., SOLOMON, 1973;CANAS and MITCHELL, 1978;CANAS et al, 1980;CANAS and MITCHELL, 1981;CANAS, 1982) have shown that the Q structure is a function of the oceanic sea floor age, the Q values being lower as the oceanic regions become younger.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies of Q in the Earth were primarily based on the decay of free oscillation peaks and long-period surface wave amplitudes (e.g. Anderson et al, 1965;Canas & Mitchell, 1978;Anderson & Hart, 1978;Sailor & Dziewonski, 1978. They established that attenuation in shear largely dominates over attenuation associated to bulk deformation, meaning that Q μ << Q κ almost anywhere in the Earth.…”
Section: Description Of Seismic Wave Attenuation Basic Observables Amentioning
confidence: 99%